If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2g + 7 + 4 = g + -6 + 4g + -1 Reorder the terms: 7 + 4 + 2g = g + -6 + 4g + -1 Combine like terms: 7 + 4 = 11 11 + 2g = g + -6 + 4g + -1 Reorder the terms: 11 + 2g = -6 + -1 + g + 4g Combine like terms: -6 + -1 = -7 11 + 2g = -7 + g + 4g Combine like terms: g + 4g = 5g 11 + 2g = -7 + 5g Solving 11 + 2g = -7 + 5g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-5g' to each side of the equation. 11 + 2g + -5g = -7 + 5g + -5g Combine like terms: 2g + -5g = -3g 11 + -3g = -7 + 5g + -5g Combine like terms: 5g + -5g = 0 11 + -3g = -7 + 0 11 + -3g = -7 Add '-11' to each side of the equation. 11 + -11 + -3g = -7 + -11 Combine like terms: 11 + -11 = 0 0 + -3g = -7 + -11 -3g = -7 + -11 Combine like terms: -7 + -11 = -18 -3g = -18 Divide each side by '-3'. g = 6 Simplifying g = 6
| (6x^2y-8xy)+(6x^2y-2xy)= | | 5-2(9+x)=x-46 | | 3h-4=2h+19 | | (5x^3-9x^2+9x)-(2x^2+6x+6)= | | 117-7x=11x+15 | | 6+3x=4-5x | | (7x^2y-4xy)+(10x^2y-8xy)= | | 16x-2=40x+4 | | 245-125= | | 12x-8=24x+1 | | 4(x-9)=(x+3) | | 6(2z-3)-2z=-5(z-2)+2 | | (2x-y)-16i=10+4yi | | 1/3(21-3a)=6-a | | 4ln(x-3)=0 | | 4x-7=3x-5 | | 5p-5=2p+4 | | 7(e+3)-4e=4(e+6)+1 | | 8x-3=2(x-1) | | 9+8x=86+5 | | -9(4y-7)=3-5y | | 6(x+5)=3(2x+5)+15 | | 8e+16=5e-17 | | 5(x-4)=2(2x+5) | | 3x+10=2x+10 | | (x+1)(x-5)(x-7)=0 | | f+(-3)=9 | | 2y=-5y-49 | | -14+y=2 | | -4(t-3)-2(-7t-8)=9(t+2)+4 | | 36(x-144)=72 | | 15x+26-2x=6x+61 |